Determinants of vascular structure and function in at-risk children born to mothers managed for pre-eclampsia (FINNCARE study) - Renlund, Michelle; Jääskeläinen, Tiina; Kivelä, Anni; Heinonen, Seppo; Laivuori, Hannele; Sarkola, Taisto (Frontiers in Cardiovascular Medicine, 2023)
Background and Aim: Pre-eclampsia (PE) is related with elevated blood pressure (BP) in children. The aim was to study if elevated BP is reflected in child arterial health and how this is influenced by anthropometrics and body composition, gestational and perinatal factors. Methods: In this prospective cohort study we assessed arteries in 182 PE exposed (46 early-onset with diagnosis before 34 gestational weeks, and 136 late-onset) and 85 unexposed (non-PE) children at 8-12 years from delivery using ultra-high frequency ultrasound in addition to ambulatory and central BPs, body composition and anthropometrics, and tonometry-derived pulse wave velocity (PWV). Results: No differences were found in intima-media thickness (IMT), adventitia thickness (AT), lumen diameter (LD), local carotid artery stiffness, distensibility or wall stress between PE exposed and non-PE children. All children’s brachial, radial, and femoral artery IMTs were associated with 24-hour systolic BP and pulse pressure, carotid-femoral PWV and anthropometric measures. 24-hour SBP and anthropometrics, notably lean body mass, were independent predictors of peripheral artery IMTs (brachial R2=0.217, radial R2=0.208, femoral R2=0.214; p<0.001). Head circumference predicted carotid artery IMT and LD (β=0.163, p=0.009; β=0.417, p<0.001, respectively), but carotid artery IMT was not associated with BP. No independent associations were found for peripheral artery ATs. Local carotid artery stiffness, distensibility and wall stress were independently associated with adiposity. No significant associations were found between gestational or perinatal factors and child vascular health parameters. Conclusions: PE exposed children’s peripheral artery IMT is similar to non-PE, but associated with BP. Adiposity is related with local carotid artery stiffness. These adverse associations in arterial health may reflect early progression of cardiovascular disease in PE exposed children.